Theoretical study of synergistic effects between anion–π and metal–Lp interactions1. Issue 94 (14th October 2015) - Gao, Meng; Gao, Guanqing; Li, Qingzhong; Yang, Xin; Li, Wenzuo; Cheng, Jianbo
<x xml:space="preserve">Abstract</x> Interesting cooperativity effects are observed when the anion–π and coinage-metal–Lp interactions coexist in the same multicomponent.